2020
DOI: 10.1001/jamaoncol.2019.5367
|View full text |Cite
|
Sign up to set email alerts
|

Use of Immunotherapy With Programmed Cell Death 1 vs Programmed Cell Death Ligand 1 Inhibitors in Patients With Cancer

Abstract: Immune checkpoint inhibitors of programmed cell death 1 (PD-1) and its ligand (PD-L1) have led to a paradigm shift in cancer treatment. Understanding the clinical efficacy and safety profile of these drugs is necessary for treatment strategy in clinical practice.OBJECTIVE To assess the differences between anti-PD-1 and anti-PD-L1 regarding efficacy and safety shown in randomized clinical trials across various tumor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
187
6
9

Year Published

2020
2020
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(238 citation statements)
references
References 62 publications
8
187
6
9
Order By: Relevance
“…In addition, although a previous mirror meta-analysis found that PD-1 inhibitors exhibited better survival outcomes than PD-L1 inhibitors in patients with solid tumors, 19 our meta-analysis demonstrated no significant differences between PD-1 and PD-L1 inhibitors plus chemotherapy for patients with ES-SCLC, in terms of ORR, PFS and OS. However, the findings were obtained from indirect analysis.…”
Section: Discussioncontrasting
confidence: 82%
“…In addition, although a previous mirror meta-analysis found that PD-1 inhibitors exhibited better survival outcomes than PD-L1 inhibitors in patients with solid tumors, 19 our meta-analysis demonstrated no significant differences between PD-1 and PD-L1 inhibitors plus chemotherapy for patients with ES-SCLC, in terms of ORR, PFS and OS. However, the findings were obtained from indirect analysis.…”
Section: Discussioncontrasting
confidence: 82%
“…Immune checkpoint inhibitors (ICIs) targeting programmed cell death 1 (PD-1), its ligand 1 (PD-L1) and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), including nivolumab, atezolizumab, and ipilimumab etc., have been increasingly applied in treating several kinds of cancers because of their evident efficacy [1,2]. Although the use of ICIs has brought survival benefits to cancer patients, the efficacy of ICIs varies widely among cancer patients during clinical practice with some patients experiencing a poor prognosis because of ICIs resistance [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this decade, many reported clinical trials for immunotherapy in various solid cancer types, including earlier challenging cancers, revealed an increase in OS and considerable strength in the treatment of NSCLC, in either combination or monotherapy (12,13). The present study, which is a populationbased study that used the SEER database, reveals good survival benefits in advanced NSCLC, which were largely attributable to the introduction of immunotherapeutic drugs to therapeutic regimens.…”
Section: Discussionmentioning
confidence: 50%